Effect of supplementary food on suckling patterns and ovarian activity during lactation. Issue 6294 (19th September 1981) - Howie, P W; McNeilly, A S; Houston, M J; Cook, A; Boyle, H
Abstract : Patterns of infant feeding, basal prolactin concentrations, and ovarian activity were studied longitudinally in 27 breast-feeding mothers from delivery until first ovulation. Suckling frequency (6.1 feeds/day) and suckling duration (122 mins/day) reached peak values four weeks post partum and remained relatively constant until the introduction of supplementary food at a mean of 16 weeks post partum. There were subsequently sharp declines in both the frequency and duration of suckling, both of which correlated closely with basal prolactin concentrations. None of the 27 mothers ovulated during unsupplemented breast-feeding, but within 16 weeks of introducing supplements ovarian follicular development had returned in 20 and ovulation in 14 mothers. The mothers who ovulated within 16 weeks of giving supplements had reduced frequency and duration of suckling more quickly and weaned more abruptly than those who continued to suppress ovulation. These data suggest that the introduction of supplementary food may exert an important and hitherto unrecognised effect on the timing of first ovulation by reducing the frequency and duration of suckling episodes.